USULAN PERBAIKAN SISTEM KESELAMATAN KERJA KARYAWAN BAGIAN PRODUKSI DENGAN MENGGUNAKAN METODE JOB SAFETY ANALYSIS (JSA) (Studi Kasus : PT. XYZ) - Muhammad Nur; sofian sofian (Research Center University of Pahlawan Tuanku Tambusai, 2020)
PT. XYZ is a company engaged in oil palm plantations and processing into semi-finished products in the form of Crude Palm Oil (CPO), palm oil processing process that accompanied the development of palm oil production in between can have a negative impact on employee safety. It can be seen from some of the data such accidents such as minor injuries, injuries of moderate to with severe injuries. It is therefore necessary identifying the causes of accidents and analyze the problems to improve and maintain the safety, employee safety and minimize the extent of occupational accidents that may occur during the production by using Job Safety Analysis (JSA). The conclusion that can be drawn based on the calculation of Statistics Accidents at accident data with a look at the numbers work accident frequency (F) and the number of work accidents severity (S) note that Sterilizer station that has the highest accident rate by 7 occupational accidents for four years with a severity of 343 days, while the JSA indicate that the station needed some proposed improvements Sterilizer form of repair machinery or equipment, personal protective equipment and alternative replacement of machinery or equipment that is more secure.